Manajemen Hubungan Masyarakat dalam Pendidikan Berdasarkan Persperktif Al-Qur'an - Abdullah; Jannah, Misbahol; Naemuddin, Rusdi; Khasanah, Atik; Rizkianti, Sofiatur (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
Public relations in education is a communication between schools and the community both inside and outside the school. This research is presented in the form of an article using a qualitative approach (library research) with the thematic modu'i method. The purpose of this study is to be able to describe social relations from the perspective of the Qur'an about public relations in schools to deepen public trust in education or organizations. The results of the study indicate that 1) Public relations can create chemistry between each other, 2) There are several verses of the Qur'an that explain public relations, namely; Q.S. Al-Fath verse 8, Q.S. Al-Maidah verse 67, Q.S. Al-Maidah verse 2, Q.S. Adz-Dzariyat verse 55.